1989
DOI: 10.1056/nejm198907273210403
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parathyroid Tumors in Multiple Endocrine Neoplasia Type 1 with Loss of Alleles on Chromosome 11

Abstract: Familial multiple endocrine neoplasia type 1 (MEN-1) is an autosomal dominant disorder characterized by the combined occurrence of tumors of the parathyroid glands, the pancreas, and the pituitary gland. Pancreatic tumors have previously been shown to be associated with the loss of alleles on chromosome 11; we therefore looked for similar genetic alterations in specimens of parathyroid tumors, which are the most common feature of MEN-1. We obtained parathyroid tumors and peripheral-blood leukocytes from six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
155
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(164 citation statements)
references
References 29 publications
6
155
0
2
Order By: Relevance
“…The sporadic pancreatic tumour presumably involved a mutation and a deletion of the normal allele in a similar manner except that both these chromosomal alterations occurred in the somatic cells. These conclusions are consistent with Knudson's two-hit theory of carcinogenesis (Knudson et al, 1976) and are supported by the findings for sporadic and familial (MEN-l associated) parathyroid tumours which have also been shown to have allelic loss within chromosome band 11q13 (Friedman et al, 1989;Thakker et al, 1989). It is possible in MEN-1, however, that the second lesion may not be at the putative disease locus, a situation analagous to that found in Wilm's tumour, where there is loss of heterozygosity which does not seem to be at the site of the gene which leads to inherited susceptibility.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The sporadic pancreatic tumour presumably involved a mutation and a deletion of the normal allele in a similar manner except that both these chromosomal alterations occurred in the somatic cells. These conclusions are consistent with Knudson's two-hit theory of carcinogenesis (Knudson et al, 1976) and are supported by the findings for sporadic and familial (MEN-l associated) parathyroid tumours which have also been shown to have allelic loss within chromosome band 11q13 (Friedman et al, 1989;Thakker et al, 1989). It is possible in MEN-1, however, that the second lesion may not be at the putative disease locus, a situation analagous to that found in Wilm's tumour, where there is loss of heterozygosity which does not seem to be at the site of the gene which leads to inherited susceptibility.…”
supporting
confidence: 88%
“…Recently, both parathyroid and pancreatic lesions in MEN-1 have been reported to show allelic loss of heterozygosity on chromosome 11 (Larson et al, 1988;Friedman et al, 1989;Thakker et al, 1989;Yoshimoto et al, 1989). In the case of the parathyroid, a similar change was reported with sporadic adenoma (Friedman et al, 1989).…”
mentioning
confidence: 99%
“…The gene had been postulated to be a tumour suppressor, as loss of the wild-type allele was found in tumours from MEN1 patients (Larsson et al, 1988). Additional support for its role as a tumour suppressor gene came from the demonstration of loss of heterozygosity in sporadic tumours (Friedman et al, 1989;Thakker et al, 1989;Sawicki et al, 1992;Debelenko et al, 1997b) and is now con®rmed by the identi®cation of somatic MEN1 mutations Zhuang et al, 1997a, b;Toilat et al, 1997;Debelenko et al, 1997a;Farnebo et al, 1998). Inactivating mutations have been reported in half of the parathyroid, pituitary and pancreatic tumours which exhibit a concomitant loss of one MEN1 allele.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple endocrine neoplasia type 1 (MENI) gene maps to 1 1q13 (Larsson et al, 1988;Fujimori et al, 1992) and LOH on 1 lq has been reported in MENl-associated tumours (Friedman et al, 1989;Thakker et al, 1989). In most cases, all informative probes on 1 lq showed LOH, but given the linkage data, the tumour suppressor gene is likely to be in 1Iq13.…”
mentioning
confidence: 99%